Predictability of Weather and Climate. Issue 7 (24th July 2019) - Krishnamurthy, V.
Abstract: The past developments in the predictability of weather and climate are discussed from the point of view of nonlinear dynamical systems. The problems ahead for long‐range predictability extending into the climate time scale are also presented. The sensitive dependence of chaos on initial conditions and the imperfections in the models limit reliable predictability of the instantaneous state of the weather to less than 10 days in present‐day operational forecasts. The existence of slowly varying components such as the sea surface temperature, soil moisture, snow cover, and sea ice may provide basis for predicting certain aspects of climate at long range. The regularly varying nonlinear oscillations, such as the Madden‐Julian Oscillation, monsoon intraseasonal oscillations, and El Niño‐Southern Oscillation, are also possible sources of extended‐range predictability at the climate time scale. A prediction model based on phase space reconstruction has demonstrated that monsoon intraseasonal oscillation can be better predicted at long leads. Key Points: The predictability of weather forecast models is limited to less than 10 days because of the limit imposed by chaos and model imperfections The existence of slowly varying components of the climate system and regularly varying phenomena provide basis for climate predictability A prediction model of monsoon intraseasonal oscillation using phase space reconstruction shows that some aspects of climate can be predicted